SEXUAL REPRESENTATION IN THE POSTMODERN PHILSOPHICAL DISCOURSE - Iryna A. Koliieva (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the article is to discover the peculiarities of the interpretation of sexual representation in the postmodern philosophical discourse; to analyze the way of becoming the category of sexuality an integral part of feminine subjectivity; to compare the ways of interpretation of the category of sexuality in the works of the Western and Ukrainian researchers. Methods and approaches. To investigate the theoretical framework in the postmodern philosophy the cross-disciplinary approach is used. The comparative approach is methodologically important to clarify the problems concerning feminine subjectivity. The very approach provides the researcher with the opportunity to review the cultural peculiarities of the given historical period. Scientific novelty. Following the peculiarities of the gender approach it was discovered that the modern interpretation of the category of feminine subjectivity includes not only racial, class and ethnical differences, but the peculiarities of a sexual character. Unfortunately, the category of sexuality is still the way of women’s oppression. Nevertheless, this category is now an important tool when representing the versatile nature of feminine subjectivity. The problems of sexual marginality are considered to be the way of destroying gender stereotypes. Conclusion. It is proved that the postmodern philosophical discourse has contributed serious transformations when interpreting the feminine nature and changed the attitude to the very category of sexuality. The interpretation of the category of sexuality is a certain touchstone clarifying the attitude towards a human being in general and towards a woman in particular. It is determined that nowadays the problems of sexuality raise some concerns and anxiety posing more questions than giving the answers. One point is absolutely clear: it is impossible to investigate the nature of a modern human being out of the postmodern philosophical discourse. What is more, it is impossible to investigate the postmodern philosophical discourse out of the categories of human sexual representation.